The type III secretion system facilitates systemic infections of Pseudomonas aeruginosa in the clinic - Tiantian Wu; Zhenchuan Zhang; Tong Li; Xu Dong; Dan Wu; Lixia Zhu; Kaijin Xu; Ying Zhang (Microbiology Spectrum, 2024)
ABSTRACT Pseudomonas aeruginosa is a major opportunistic pathogen that can cause severe systemic infections. Here, we found that the type III secretion system effector ExoU was the main determinant of pathogenicity of a highly virulent clinical isolate strain, BSI_S5, of P. aeruginosa, which caused severe bloodstream infections and belongs to ST463/O4. Deletion of exoU showed significantly attenuated cytotoxicity and virulence in vivo, while deletion of two other unique genes from strain BSI_S5, chr_1696 and chr_4238, which encodes type I secretion system permease/ATPase or polysaccharide biosynthesis protein, respectively, caused no apparent loss of toxicity compared to the parent strain, and complementation of the ΔexoU mutant restored its virulence. The presence of ExoU-induced lung lesions and the mucosal damage of gallbladder in mice, and the replication of the ΔexoU mutant was hindered in vivo compared with the parent strain. We show here for the first time that a clinical isolate with intact exoU harbored a mutation of T→G substitution in the adjacent specific Pseudomonas chaperone for ExoU (spcU), which caused phenylalanine to valine change at amino acid 94 of SpcU, resulting in significant loss of cytotoxicity. This finding suggests that intact exoU is not sufficient for cytotoxicity, but a functional downstream SpcU is required for ExoU secretion and cytotoxicity. Finally, we found that BSI_S5 harbored two types of insertion sequences adjacent to exoU, suggesting the potential of exoU to be transferred to other strains. Our study opens an avenue for further mechanistic study of P. aeruginosa systemic infections regarding its high pathogenicity and clinical spread. IMPORTANCE The identification of decisive virulence-associated genes in highly pathogenic P. aeruginosa isolates in the clinic is essential for diagnosis and the start of appropriate treatment. Over the past decades, P. aeruginosa ST463 has spread rapidly in East China and is highly resistant to β-lactams. Given the poor clinical outcome caused by this phenotype, detailed information regarding its decisive virulence genes and factors affecting virulence expression needs to be deciphered. Here, we demonstrate that the T3SS effector ExoU has toxic effects on mammalian cells and is required for virulence in the murine bloodstream infection model. Moreover, a functional downstream SpcU is required for ExoU secretion and cytotoxicity. This work highlights the potential role of ExoU in the pathogenesis of disease and provides a new perspective for further research on the development of new antimicrobials with antivirulence ability.